Enhancing children’s nutrition: the influence of rural household technology under China’s home appliances going to the countryside policy - Du, Mingling; Shi, Junhui; Shi, Songping; Wang, Fang (Frontiers in Nutrition, 2024)
This study explores the influence of household technological advancements on children's nutritional intake, specifically within the context of the Chinese government's "Home Appliances Going to the Countryside" (HAGC) initiative. Utilizing data from the China Health and Nutrition Surveys of 2006, 2009, and 2011, we employed a Propensity Score Matching Difference-in-Differences (PSM-DID) framework to ascertain the repercussions of enhanced household technology on the dynamics of children's nutritional consumption patterns. Our analysis reveals that the HAGC-inspired integration of household appliances, including color televisions, washing machines, and refrigerators, has beneficially reshaped the nutritional consumption patterns of children, with a pronounced effect among female children. This finding remains consistent even when employing alternate methodological robustness tests. A deeper examination of the HAGC policy's mechanisms underscores the pivotal roles of parental time allocation, improved food storage capabilities, and augmented information accessibility as significant drivers bolstering children's nutritional intake. These insights bear considerable significance for strategizing interventions aimed at elevating the nutritional well-being of children in rural settings, offering valuable input for shaping public health policies tailored for such demographies.